Evaporation from undulating soil surfaces under turbulent airflow through numerical and experimental approaches - Gao, B. (2020)
The model explicitly describes the relevant physical processes and the key properties in the free flow, porous media, and at the interface, allowing for the analysis of coupled exchange fluxes. An experiment aiming to simultaneously collect the data of the boundary layer and soil evaporation in the area around the soil–atmosphere interface was conducted using a wind tunnel integrated with a soil tank. The turbulent boundary layer above the undulating soil surface was captured using high‐resolution hot‐wire anemometry, confirming the presence of recirculation zones in the undulating valleys and locally low evaporative flux. Experimental data were used to validate the extended model, and modeling results demonstrate that turbulent airflow enhances evaporation and shortens the duration of Stage I. The surface geometry significantly affects the local evaporative flux by influencing the vapor distribution, concentration gradient, and water availability at the soil surface, especially when recirculation zones form in the valleys. As a joint result of turbulence and surface undulations, the influence of wind speed on both the local and system‐level evaporation rate is restricted.